Frequência de marcadores de Hepatites Virais (A,B e C) observada no período de Junho a Agosto de 1994: (Laboratório Bio-Ciência Lavoisier) - Bassinello, Patrícia; Rodrigues, Patrícia Soares; Vaz, Adelaide (Brazilian Journal of Sexually Transmitted Diseases, 1995)
Hepatitis is an inflammation ofthe liver caused by certain viruses and other factors, such as drugs abuse, some medication, and trauma. However, most types of virai hepatitis have a pauce syrnptomatic course. Many cases of hepatitis are not life threatening, the forms which are cronic can lead to li ver failure and death. ln a three-month period (Jume to August 94), were analysed for the diferents markers of virai hepatitis through ELISA tests, 589 patients (302 male and 287 female; 545 adults and 44 children). Among 589 patients, 150 were solicitation for hepatitis A (HAV), 301 for hepatitis (HBV) and 134 for hepatitis C (HCV). Toe results obtained through these tests were discussed here.